Effect of an intense period of competition on race performance and self‐reported illness in elite cross‐country skiers. Issue 6 (27th March 2015) - Svendsen, I. S.; Gleeson, M.; Haugen, T. A.; Tønnessen, E.
Abstract : The aim of this study was to determine whether participating in a cross‐country skiing stage race (Tour de Ski; TDS) affects subsequent illness incidence, training, and race performance. Self‐reported training and illness data from 44 male and female elite cross‐country skiers were included. In total, 127 years of data were collected (2–3 seasons per athlete). Illness incidence, training load, and performance in international competitions were calculated for athletes who did and did not participate in TDS. Forty‐eight percent of athletes reported becoming ill during or in the days immediately after taking part in TDS vs 16% of athletes who did not participate. In both groups, illness incidence was somewhat lower for female athletes. For male athletes, race performance was significantly worse for 6 weeks following TDS vs 6 weeks before TDS. Furthermore, while female athletes who participated in TDS performed relatively better than controls in Olympics/World Championships, male athletes who participated in TDS typically performed worse in subsequent major championships. Participating in TDS appears to result in ∼ 3‐fold increase in risk of illness in this period. Male athletes appear more prone to illness and also see a drop in race performance following TDS, possibly linked to differences in training load before and after the event.